Tính :\(\sqrt{15+2\sqrt{35}+\sqrt{60}+\sqrt{84}}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\sqrt{15+2\sqrt{35}+\sqrt{60}+\sqrt{84}}\)
= \(\sqrt{15+2\sqrt{35}+2\sqrt{15}+2\sqrt{21}}\)
= \(\sqrt{3+5+7+2\sqrt{5}\sqrt{7}+2\sqrt{3}\sqrt{5}+2\sqrt{3}\sqrt{7}}\)
= \(\sqrt{\left(\sqrt{3}+\sqrt{5}+\sqrt{7}\right)^2}\)
= \(\sqrt{3}+\sqrt{5}+\sqrt{7}\)
b.
ĐKXĐ: \(x\ge-1\)
\(\sqrt{\left(x+1\right)\left(x+35\right)}-14\sqrt{x+35}+84-6\sqrt{x+1}=0\)
\(\Leftrightarrow\sqrt{x+1}\left(\sqrt{x+35}-14\right)-6\left(\sqrt{x+35}-14\right)=0\)
\(\Leftrightarrow\left(\sqrt{x+1}-6\right)\left(\sqrt{x+35}-14\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{x+1}=6\\\sqrt{x+35}=14\end{matrix}\right.\)
\(\Leftrightarrow...\)
a. ĐKXĐ: \(-1\le x\le1\)
Đặt \(\left\{{}\begin{matrix}\sqrt{x+1}=a\ge0\\\sqrt{1-x}=b\ge0\end{matrix}\right.\)
\(\Rightarrow a+2a^2=-b^2+b+3ab\)
\(\Leftrightarrow\left(2a^2-3ab+b^2\right)+a-b=0\)
\(\Leftrightarrow\left(a-b\right)\left(2a-b\right)+a-b=0\)
\(\Leftrightarrow\left(a-b\right)\left(2a-b+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}a=b\\2a+1=b\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{x+1}=\sqrt{1-x}\\2\sqrt{x+1}+1=\sqrt{1-x}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\4x+5+4\sqrt{x+1}=1-x\left(1\right)\end{matrix}\right.\)
(1) \(\Leftrightarrow4\sqrt{x+1}=-4-5x\) \(\left(x\le-\dfrac{4}{5}\right)\)
\(\Leftrightarrow16\left(x+1\right)=25x^2+40x+16\)
\(\Leftrightarrow25x^2+24x=0\Rightarrow\left[{}\begin{matrix}x=0\left(loại\right)\\x=-\dfrac{24}{25}\end{matrix}\right.\)
\(a,8+2\sqrt{15}=\left(\sqrt{3}+\sqrt{5}\right)^2\\ b,12+2\sqrt{35}=\left(\sqrt{7}+\sqrt{5}\right)^2\\ c,8+\sqrt{60}=8+2\sqrt{15}=\left(\sqrt{3}+\sqrt{5}\right)^2\)
2\(\left(\sqrt{28}-2\sqrt{3}+\sqrt{7}\right)\sqrt{7}+\sqrt{84}\)
= \(14-\sqrt{84}+7-\sqrt{84}\)
= 21
Ta có: \(\dfrac{8+2\sqrt{15}+\sqrt{21}+\sqrt{35}}{\sqrt{3}+\sqrt{5}+\sqrt{7}}\)
\(=\dfrac{\left(\sqrt{3}+\sqrt{5}\right)^2+\sqrt{7}\left(\sqrt{3}+\sqrt{5}\right)}{\sqrt{3}+\sqrt{5}+\sqrt{7}}\)
\(=1+\sqrt{3}+\sqrt{5}\)
ĐK: \(x\ge-1\)
pt <=> \(\left(14\sqrt{x+35}-84\right)+\left(6\sqrt{x+1}-\sqrt{x^2+36x+35}\right)=0\)
<=> \(14\left(\sqrt{x+35}-6\right)+\sqrt{x+1}\left(6-\sqrt{x+35}\right)=0\)
<=> \(\left(\sqrt{x+35}-6\right)\left(11-\sqrt{x+1}\right)=0\)
<=> \(\orbr{\begin{cases}\sqrt{x+35}-6=0\\11-\sqrt{x+1}=0\end{cases}}\)Em làm tiếp nhé!
`1)A=sqrt{4+sqrt{10+2sqrt5}}+sqrt{4-sqrt{10+2sqrt5}}`
`<=>A^2=4+sqrt{10+2sqrt5}+4-sqrt{10+2sqrt5}+2sqrt{16-10-2sqrt5}`
`<=>A^2=8+2sqrt{6-2sqrt5}`
`<=>A^2=8+2sqrt{(sqrt5-1)^2}`
`<=>A^2=8+2(sqrt5-1)`
`<=>A^2=6+2sqrt5=(sqrt5+1)^2`
`<=>A=sqrt5+1(do \ A>0)`
`b)B=sqrt{35+12sqrt6}-sqrt{35-12sqrt6}`
Vì `35+12sqrt6>35-12sqrt6`
`=>B>0`
`B^2=35+12sqrt6+35-12sqrt6-2sqrt{35^2-(12sqrt6)^2}`
`<=>B^2=70-2sqrt{361}`
`<=>B^2=70-2sqrt{19^2}=70-38=32`
`<=>B=sqrt{32}=4sqrt2(do \ B>0)`
`3)(4+sqrt{15})(sqrt{10}-sqrt6)sqrt{4-sqrt{15}}`
`=sqrt{4+sqrt{15}}.sqrt{4-sqrt{15}}.sqrt{4+sqrt{15}}(sqrt{10}-sqrt6)`
`=sqrt{16-15}.sqrt2(sqrt5-sqrt3).sqrt{4+sqrt{15}}`
`=sqrt{8+2sqrt{15}}(sqrt5-sqrt3)`
`=sqrt{5+2sqrt{5.3}+3}(sqrt5-sqrt3)`
`=sqrt{(sqrt5+sqrt3)^2}(sqrt5-sqrt3)`
`=(sqrt5+sqrt3)(sqrt5-sqrt3)`
`=5-3=2`
\(15+2\sqrt{35}+2\sqrt{15}+2\sqrt{21}=3+5+7+\left(2\sqrt{3}.\sqrt{5}+2\sqrt{5}.\sqrt{7}+2\sqrt{7}.\sqrt{3}\right)\)
\(=\left(\sqrt{3}+\sqrt{5}+\sqrt{7}\right)^2\)